Myeloperoxidase Negatively Regulates Neutrophil–Endothelial Cell Interactions by Impairing αMβ2 Integrin Function in Sterile Inflammation - Tseng, Alan; Kim, Kyungho; Li, Jing; Cho, Jaehyung (Frontiers in Medicine, 2018)
Interactions of neutrophils with endothelial cells and platelets contribute to tissue damage and vascular occlusion under sterile inflammatory conditions. However, the molecular mechanisms regulating the cell-cell interactions remain poorly understood. Previous studies suggest that reactive oxygen species (ROS), such as H2O2, produced from NADPH oxidase 2 play a critical role in platelet-neutrophil interactions by regulating the function of neutrophil αMβ2 integrin during sterile inflammation. In this study, we further demonstrate a crucial role for myeloperoxidase (MPO) in regulating the adhesive function of neutrophils through αMβ2 integrin. Using real-time fluorescence intravital microscopy and in vitro assays, we showed that loss of MPO promoted neutrophil-endothelial cell interactions and neutrophil emigration but did not affect neutrophil-platelet interactions under inflammatory conditions. Using genetic and pharmacologic approaches, we found that following agonist stimulation, MPO knockout (KO) neutrophils exhibited a significant increase in extracellular hydrogen peroxide (H2O2) and surface level of αMβ2 integrin and that these effects were dependent on MPO activity. Our in vivo studies using an ischemia/reperfusion-induced hepatic inflammation model revealed that compared to WT mice, MPO KO neutrophils displayed a pro-migratory phenotype while ameliorating tissue damage. These results suggest that MPO plays a negative role in the adhesive and migratory function of neutrophils by impairing αMβ2 integrin function under sterile inflammatory conditions.